A new species of the genus Proctogastrolaelaps McGraw & Farrier (Acari: Melicharidae) from the Far East of Russia, and contributions to knowledge of this genus - Joharchi, Omid; Marchenko, Irina I.; Döker, Ismail; Khaustov, Vladimir A. (Zootaxa, 2021)
We describe a new mite species from the Far East of Russia—Proctogastrolaelaps subsolanus Joharchi & Marchenko sp. nov. (Acari: Melicharidae). The new species was collected from soil-litter on the shores of the Tunaycha Lake and Sea of Okhotsk in Sakhalin Island. The important morphological characteristics of the genus Proctogastrolaelaps are revised.